Flexural and tensile behavior of rubberized concrete: experimental analysis - Loubna Enkaiki; Oussama Jarachi; Petru Mihai; Hanane Moulay Abdelali; Om El Khaiat Moustachi (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2025)
The escalating accumulation of rubber waste, especially from end-of-life tires, represents a very significant and pressing environmental challenge that requires particular attention from environmental organizations worldwide, as well as industries, to minimize its negative effects on ecosystems, human well-being, and the planet’s long-term sustainability as much as possible. The goal of this study is to explore a sustainable solution by introducing crumb rubber into a concrete mixture and evaluate its feasibility for structural applications. Thus, crumb rubber was introduced at different percentages by volume (0%, 10%, 20%, and 30%) to examine its effect on density, splitting tensile strength, and flexural behavior. The results shed light on the potential of rubberized concrete as an eco-friendly substitute while addressing its challenges. In fact, at 30% of crumb rubber content, density decreased by 5.6%, while splitting tensile strength decreased by 45%. However, beam flexural breaking strength marginally decreased by 9%, and deflection at mid-span decreased by around 13% for 30% of crumb rubber content. The failure mode evolved from brittle in concrete to slightly ductile with increased rubber content. The cracks observed in both reference concrete and rubberized concrete were similar, implying that the introduction of rubber did not result in a significant change in the overall behavior of the concrete at ultimate strength.